2000
DOI: 10.1038/73128
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of insulin-dependent diabetes using islets generated in vitro from pancreatic stem cells

Abstract: Ductal structures of the adult pancreas contain stem cells that differentiate into islets of Langerhans. Here, we grew pancreatic ductal epithelial cells isolated from prediabetic adult non-obese diabetic mice in long-term cultures, where they were induced to produce functioning islets containing alpha, beta and delta cells. These in vitro-generated islets showed temporal changes in mRNA transcripts for islet cell-associated differentiation markers, responded in vitro to glucose challenge, and reversed insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
402
0
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 648 publications
(432 citation statements)
references
References 36 publications
18
402
0
8
Order By: Relevance
“…In 2000 Peck and colleagues showed that it was possible to cultivate and expand a cell with neuroendocrine-type morphology from the mouse pancreas that could then give rise to isletlike clusters expressing insulin and glucagon (Ramiya et al, 2000). When implanted into the subcapsular region of the kidney of diabetic female NOD/Uf mice, (although they had slightly elevated blood glucose levels relative to controls) they survived insulin-free for up to 55 days.…”
Section: Islet Neogenesis: the Current Hypothesesmentioning
confidence: 99%
“…In 2000 Peck and colleagues showed that it was possible to cultivate and expand a cell with neuroendocrine-type morphology from the mouse pancreas that could then give rise to isletlike clusters expressing insulin and glucagon (Ramiya et al, 2000). When implanted into the subcapsular region of the kidney of diabetic female NOD/Uf mice, (although they had slightly elevated blood glucose levels relative to controls) they survived insulin-free for up to 55 days.…”
Section: Islet Neogenesis: the Current Hypothesesmentioning
confidence: 99%
“…Stem cells capable of reconstituting the tissues in which they reside include myosatellite cells in skeletal muscle (Grounds, 1999), chondroblasts in the perichondrium surrounding cartilage (Yotsuyanagi et al, 1999), oval cells in the liver (Gordon et al, 2000), preductal stem cells in the pancreas (Bonner-Wier et al, 2000;Ramiya et al, 2000), basal stem cells of epithelial tissues (Slack, 2000), and neuronal stem cells in the brain (Gage, 2000). By contrast, other studies have shown that stem cells residing in one tissue can differentiate into cell types of another tissue.…”
mentioning
confidence: 99%
“…The endocrine compartment consists of the islets of Langerhans, which contain clusters of studies have shown the existence of pancreatic stem cells [2,3,4,5], these cells have not yet been isolated from the pancreas in a pure form.…”
mentioning
confidence: 99%